Borrelia, Leishmania, and Babesia: An Emerging Triad of Vector-Borne Co-Infections? - Elianne Piloto-Sardiñas; Ana Laura Cano-Argüelles; Alejandro Cabezas-Cruz (Pathogens)
Canine leishmaniosis (CanL), caused by the protozoan Leishmania infantum and transmitted primarily by phlebotomine sand flies, poses significant challenges for zoonotic disease management [...]